Modification of ASTM B107 AZ31 alloy with TiO2 particles using the dip-coating method (2018)
Introduction− Magnesium alloys have been known for its bio-compatible characteristics and tissue restoration properties. On the other hand, TiO2 has been found to decrease the corrosion rates of the magnesium alloys.Objective−In this work, the dip-coating technique was used to coat the magnesium alloy with TiO2 particles in order to evalu-ate its corrosion resistance.Methodology−The particles were analyzed by Scanning Elec-tron Microscopy (SEM) and visual inspection. Additionally, hy-drogen evolution tests were performed to understand the effect of adding TiO2 in corrosion rates of Mg-alloys.Results− The results showed the positive effect of TiO2 in the improvement of the ASTM B107 AZ31B Mg alloys corro-sion by an indirect measurement through hydrogen evolution tests. The bare ASTM B107 AZ31B showed a corrosion 29 times faster compared to the coated alloy. The thickness of the coatings obtained using the dip-coating method is thin-ner than 20 nm. Conclusions−TiO2 particles were aggregated on the surface of the ASTM B107 AZ31B alloy with a controlled speed. SEM images have shown the improvement of the coating when the H2O concentration in the sol increased. Another important parameter is the withdrawal speed during the dip-coat process which was found to be better at a speed of 3mm/min. Hydrogen evolution in the acid solution showed that coated ASTM B107 AZ31B has less hydrogen production during the corrosion test. The dip-coating technique can also be used to coat polypropyl-ene discs entirely.